Bio-Oil Upgrading Over Bi-Functional Catalyst in CO/H2O System - Xu, Qingli; Zhang, Hongyan; Li, Shanling; Dai, Weidi; Jiang, Jianchun; Yan, Yongjie (Asian Journal of Chemistry, 2013)
The liquid phase upgrading of a model bio-oil was studied over a series of supported Ni catalysts in the CO/H2O system. 6 % Ni/B206 catalyst showed the highest activity for deoxygenation, the oxygen content of the model oil decreasing from an initial value of 47.74 wt % to 3.76 wt % after upgrading. In addition, the reason for catalyst deactivation was investigated. The fresh and deactivation catalysts were analyzed by X-ray diffraction, Brunauer-Emmett-Teller, thermogravimetric analysis and scanning electron microscopy, which showed that the carbon deposition is the main reason for catalyst deactivation.